2013
DOI: 10.3390/v5123007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Major Structural Protein Genes of Avian Coronavirus Infectious Bronchitis Virus Isolates in Southern China

Abstract: To gain comprehensive genetic information of circulating avian coronavirus infectious bronchitis virus (IBV) isolates in China, analysis of the phylogenetic tree, entropy of the amino acid sequences, and the positive selection as well as computational recombinations of S1, M and N genes of 23 IBV isolates was conducted in the present study. The phylogenetic trees based on the S1, M and N genes exhibited considerably different topology and the CK/CH/LSC/99I-type isolates were the predominant IBVs based on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 40 publications
4
65
1
Order By: Relevance
“…It has been reported that the side effects of the 4/91 vaccine might provide the basis for recombination with other strains. This phenomenon has been shown by several studies which have traced the emergence of many novel IBV strains to recombination events between the 4/91 vaccine and field strains (Feng et al, 2018;Han et al, 2017;Jiang et al, 2017Jiang et al, , 2018Liu et al, 2013;Mo et al, 2013;Ovchinnikova et al, 2011;Zhang et al, 2015Zhang et al, , 2016Zhou et al, 2017) in cases where the 4/91 vaccine strain could not provide effective protection against the field strains , leading to coinfection of the vaccine and field strains in the same chickens and ultimately resulting in recombination. In this study, we performed complete genome sequence analysis of strains I0718/17, I0722/17, I0724/17, and I0737/17 and confirmed the occurrence of recombination events at the 5′ ends of the S1 gene between a 4/91-like virus (GI-13 lineage) and a YX10-like virus (GI-19) (Xu et al, 2018), which contributed to the emergence of the IBV strains.…”
Section: Discussionmentioning
confidence: 87%
“…It has been reported that the side effects of the 4/91 vaccine might provide the basis for recombination with other strains. This phenomenon has been shown by several studies which have traced the emergence of many novel IBV strains to recombination events between the 4/91 vaccine and field strains (Feng et al, 2018;Han et al, 2017;Jiang et al, 2017Jiang et al, , 2018Liu et al, 2013;Mo et al, 2013;Ovchinnikova et al, 2011;Zhang et al, 2015Zhang et al, , 2016Zhou et al, 2017) in cases where the 4/91 vaccine strain could not provide effective protection against the field strains , leading to coinfection of the vaccine and field strains in the same chickens and ultimately resulting in recombination. In this study, we performed complete genome sequence analysis of strains I0718/17, I0722/17, I0724/17, and I0737/17 and confirmed the occurrence of recombination events at the 5′ ends of the S1 gene between a 4/91-like virus (GI-13 lineage) and a YX10-like virus (GI-19) (Xu et al, 2018), which contributed to the emergence of the IBV strains.…”
Section: Discussionmentioning
confidence: 87%
“…There have been several episodes of infectious bronchitis (IB) in Chinese chicken flocks, and the genotypes/serotypes of IBVs were previously classified based mainly on the nucleotide sequences of genes encoding the S1 subunit of the spike protein (Han et al, 2011), and in some cases based on cross virus-neutralization Chen et al, 2017) in China. Since 1995, the predominant IBV type in China has been LX4 (also known as QX-like viruses), but molecular studies have shown that new types and variants are emerging continually Mo et al, 2013;Zhao et al, 2013;Liu et al, 2014;Zhou et al, 2014;Chen et al, 2015;Xu et al, 2016;Zhang et al, 2015;Leghari et al, 2016;Chen et al, 2017;Zhao et al, 2017;Zhou et al, 2017). It has been suggested that the emergent IBV strains in China may have different origins.…”
Section: Introductionmentioning
confidence: 99%
“…The AvCoV genome consists of positive-sense single-stranded RNA with an approximate size of 27 kb (Jackwood et al, 2012). The genome is subdivided into nine open reading frames (ORFs) that encode a set of nonstructural proteins known as the transcriptase-replicase complex, which functions as the RNA polymerase (Pol-1a, -1b) and four main structural proteins (spike surface glycoprotein (S), membrane (M), envelope (E), and nucleocapsid (N)) (Fauquet et al, 2005;Mardani et al, 2008;Mo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%